2012
DOI: 10.1590/s1516-35982012000500011
|View full text |Cite
|
Sign up to set email alerts
|

Pedigree analysis on the population of Gir cattle in Northeast Brazil

Abstract: -The objective of this study was to characterize the population genetic structure of the Gir breed in the Northeast of Brazil. The data used in this study were taken from pedigree information of 8,897 Gir animals between 1957 and 2007, obtained from the Brazilian Zebu Breeders Association (ABCZ). The program ENDOG was used to estimate the parameters based on the probability gene origin. From the amount of the studied animals, 67.22%, 18.41% and 3.15% had complete pedigree only on the first, second and third pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Nowadays, herdbook information includes records of both imported animals, with their respective country, and those born in Brazil. The analysis of population structure based on pedigree information has been applied to the genetic characterization of different cattle breeds in Brazil (Faria et al, 2010;Reis Filho et al, 2010;Oliveira et al, 2012;Santana et al, 2012) as well as in several other countries (see review by Carolino and Gama, 2008) and is now a common tool in managing genetic diversity in livestock species (FAO, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, herdbook information includes records of both imported animals, with their respective country, and those born in Brazil. The analysis of population structure based on pedigree information has been applied to the genetic characterization of different cattle breeds in Brazil (Faria et al, 2010;Reis Filho et al, 2010;Oliveira et al, 2012;Santana et al, 2012) as well as in several other countries (see review by Carolino and Gama, 2008) and is now a common tool in managing genetic diversity in livestock species (FAO, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The ratio ⨍ e /⨍ a in White Shorthaired goat was 1.6. The higher the value of this ratio, the higher the bottleneck effect resulting from the decrease of the number of reproducers over the generations (de Oliviera et al 2012). When the ratio ⨍ e /⨍ a is close to unity, the population is stable in terms of effectively contributing ancestors and the bottleneck has not played a significant role in the population (Fair et al 2012).…”
Section: Methodsmentioning
confidence: 99%
“…This could be because pedigree relationships are based on expectations. Other than those, mean inbreeding coefficients for livestock reported are consistently low, generally less than 0.01 in many different breeds of cattle around the world ( Peixoto et al, 2010 ; Dang et al, 2011 ; Oliveira et al, 2012 ; Santana Junior et al, 2012 ; Steyn et al, 2012 ; Barbosa et al, 2013 ; Worede et al, 2013 ; Pavlik et al, 2014 ; Pienaar et al, 2015 ; Bernardes et al, 2016 ). Domínguez-Viveros et al (2012) presented tabular summaries as distributions of inbreeding coefficients and additive relatedness within equine and taurine populations involved in Mexican bullfighting.…”
Section: Discussionmentioning
confidence: 93%
“…Mean estimates of Wright’s relationship coefficient from the present study for the Trask 26 bulls with the different ancestor groups (range from 0.15 to 0.208) were higher than reported estimates from other cattle populations. Mean relatedness ranged from less than 0.02 in Gir ( Oliveira et al, 2012 ), Brown Swiss ( Worede et al, 2013 ), and Nellore ( Barbosa et al, 2013 ) to a high of 0.065 in Brangus cattle in Mexico ( Ramírez-Valverde et al, 2018 ). Leesburg et al (2013) reported an average relationship coefficient of 0.24 for Line 1 Hereford ( MacNeil, 2009 ) in the United States with South African Hereford cattle.…”
Section: Discussionmentioning
confidence: 99%